ANALYSIS OF THE EFFECTIVENESS OF THE TRADITIONAL TREATMENT METHOD - Boltayev Timur Shavkatovich (Journal of Medical Genetics and Clinical Biology, 2024)
The problem of treating surgical infection of soft tissues against the background of diabetes mellitus remains relevant to the present day. This is due to an increase in the number of patients with diabetes mellitus and an increase in purulent-inflammatory complications in them. It is the development of purulent complications in patients with diabetes mellitus that often cannot be avoided without surgical interventions, the postoperative mortality of which is high - up to 20%. The course of this pathology against the background of diabetes mellitus negatively affects the outcome of the disease. The purpose of our study was: to analyze the effectiveness of clinical and laboratory features of the course of purulent surgical soft tissues against the background of diabetes mellitus. 166 patients with purulent surgical diseases of soft tissues were studied. Group I consisted of 40 patients with no diabetes mellitus, group II 43 patients were on the background of diabetes mellitus. The results of the study showed: the timing of normalization of the criteria for assessing the wound process and indicators of general intoxication of the organism of groups I and II were 3 days late in patients with purulent surgical diseases of soft tissues against the background of diabetes mellitus than in patients without concomitant disease diabetes mellitus.